Influence of Poverty and HDI on Economic Growth Through Unemployment in Sulawesi, 2011–2023 - Damara, M. Deni; Noer, M. Raihan; Ananda, Bunga; Sitohang, Cindy Eleonora; Silaban, Putri Sari Margaret Julianty (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study investigates the influence of poverty and the Human Development Index (HDI) on economic growth, with unemployment serving as a mediating variable, across five provinces in Sulawesi from 2011 to 2023. Economic growth remains a critical indicator for regional development, and understanding the role of socioeconomic factors such as poverty, education, health, and labor dynamics is essential for policy formulation. The study employs a quantitative research design using panel data analysis, integrating path analysis techniques and the Sobel test to identify both direct and indirect effects among the variables. The empirical results show that poverty has no statistically significant effect on either the unemployment rate or economic growth, indicating that poverty alone may not directly influence macroeconomic performance in this context. Conversely, HDI exhibits a significant influence on both unemployment and economic growth, reinforcing the crucial role of education, health, and overall human development in shaping economic outcomes. However, the unemployment rate does not mediate the relationship between either poverty or HDI and economic growth, suggesting that other mechanisms may be more relevant in translating human development into economic progress. These findings emphasize the limited mediating role of unemployment and highlight the strategic importance of investing in human capital. As such, policy recommendations should prioritize improving access to quality education and healthcare services, while also promoting job creation programs. These initiatives are essential to foster inclusive, resilient, and sustainable economic growth across Sulawesi’s diverse provinces.